COMES HISPANIARUM W CZASACH CESARZA KONSTANTYNA WIELKIEGO - Wiewiorowski, Jacek (Zeszyty Prawnicze, 2017)
Comes Hispaniarum in the Age of Constantine the Great Summary The paper discusses the case of comites Hispaniarum, who belonged to a group of special envoys of Constantine the Great (306-337) called comites dioecesium and/or comites quiper provincias constituti sunt ox simply comites provinciarum. Those comites were first of all the emperor’s trusted collaborators, who were obliged to inform the ruler about the situation in the diocese which were not visited by him (with one exemption) and to put in order if necessary. Comites dioecesium are often mixed up or even identified by contemporary scholars with the vicars of dioceses, who had similar duties but, unlike counts, were fixed officials with more or less defined competences. The paper discusses the sources concerning the comites Hispaniarum (6 different emperor’s constitutions and two inscriptions) and the opinions of scholars concerning the vicars and the counts of the Spanish diocese. The author describes the case of agentes vices praefectus praetorio, extraordinary envoys o fpraefectus praetorio on the turn o f 3rd and 4th century A.D. often identified by modern scholars with the vicars. He stresses the difference between comites and vicarii Hispaniarum and proves that the establishment of the firm post of vicarius Hispaniarum (first mentioned in 335-336) was preceded by the period when the extraordinary envoys of Constantine - comites Hispaniarum or extraordinary substitutes of praefectus praetorio - agentes vices praefectus praetorio were sent to the diocese of Spain.